Food Security Interventions to Eradicate Extreme Poverty: Case Studies in Food Insecure Areas - Mohammad Rezza Fahlevvi; Ikra Novar Rizqi; Lina Marlina; Lelly Triatni Siregar (Civitas Consecratio: Journal of Community Service and Empowerment, 2025)
Food security remains a significant challenge for vulnerable areas, requiring sustainable interventions to improve community well-being. This community service activity aims to strengthen food security through a participatory approach involving nutrition education, local food diversification training, and program sustainability monitoring. The Participatory Action Research (PAR) method was applied, with data collected through questionnaires, in-depth interviews, and participatory observations. The results showed a significant improvement in household food security, with food insecurity rates dropping from 65% to 30%, alongside positive changes in consumption patterns. However, program sustainability still requires policy support and the involvement of local stakeholders to ensure long-term impact. The conclusion emphasizes that community-based interventions can be an effective model for enhancing food security, but sustainable strategies are essential to maintain program benefits over time.